Peningkatan Kemampuan Pengajar Dan Calon Pengajar Pada Pembelajaran Geometri Melalui Pelatihan Geogebra Dasar - Haris Kurniawan; Eva Susanti (Publikasi Pendidikan, 2023)
The covid pandemic that has hit the last 2 years has inadvertently changed the study habits and study interests of current students. Especially the need for technology in learning. Moreover, the interest and motivation of students in studying at school. Therefore, the teacher's teaching method must be adapted to the conditions and interests of students, in the hope that it can make it easier for students to understand learning. Moreover, in learning geometry, there are still many teachers in Palembang who do not have the ability to utilize technological aids in teaching geometry. Moreover, the school where teachers teach must be able to support the implementation of learning with this technology-supporting media. The purpose of this training is to equip and improve the ability of mathematics teachers to teach geometry. This training is in the form of tutorials to introduce simple tools used in basic geometry materials (points, lines, planes, and building spaces).   The methods used are presentation, practice, demonstration, and discussion methods. This training was carried out through a Zoom Meeting and was attended by 45 participants from various regions in Indonesia such as Palembang, Batam, Kalimantan, Surabaya, Jakarta, Lampung, Linggau, Pagaralam, etc. This training provides assistance to participants in using the geogebra application, then participants are given time within 1 week to complete the task of making learning media using the geogebra application. The results were very good, some participants collected assignments and learned media works from the participants who were quite creative and diverse. In addition, the response from the participants was very enthusiastic about this training judging from the questionnaire given, and hoped that there would be geogebra training in the next session